If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 34 + -1b Solving 22 = 34 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 22 + b = 34 + -1b + b Combine like terms: -1b + b = 0 22 + b = 34 + 0 22 + b = 34 Add '-22' to each side of the equation. 22 + -22 + b = 34 + -22 Combine like terms: 22 + -22 = 0 0 + b = 34 + -22 b = 34 + -22 Combine like terms: 34 + -22 = 12 b = 12 Simplifying b = 12
| 7x-5=3+4x | | 28=b(b-3) | | 2/7+2/7=-4/5v-3/5v | | sx-5=9 | | 2(2x+4)=3x+12 | | 18x^2-132x+242=0 | | 8(x+1)-11=53 | | x+0.068x= | | x+x+5+2(x+5)=431 | | 3x+-14=x | | a^2-15a-40=0 | | 33-4x=2x-3 | | 6y=4-12 | | 3a/4-7/4=4a/3+5/3 | | 3x+10=17+2x | | x+0.068= | | m^2+7m-12= | | 7/3=2w | | 4(x+1)-11=53 | | 5(x+1)-11=53 | | -6(x+1)-11=53 | | 60=-16x^2+85x | | x+2/3-1/2=x/3-2(x-2)/3 | | -3x-3(-5x-17)=17 | | -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x |